Topical Corticosteroid-Induced Iatrogenic Cushing Syndrome in an Adolescent: A Case Report - Rai, A.; Tamrakar, R.; Maskey, R. (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Cushing syndrome (CS) is an endocrinological disorder characterized by increased blood cortisol level. It is either due to an excessive endogenous release of steroids (e.g., pituitary adenoma or adrenal hyperplasia) or exogenous administration of steroids. Iatrogenic Cushing syndrome is the most common form of Cushing syndrome. The vast majority of cases are due to oral or parenteral steroid preparations, which are commonly prescribed for pulmonary, renal, hematological or autoimmune diseases. Prolonged use of topical corticosteroids, particularly in children, may cause Cushing syndrome and suppression of the hypothalamo-pituitory-adrenal (HPA) axis, which is less common than that of oral or parenteral route. Iatrogenic CS due to the overuse of topical corticosteroids is rarely reported. There are only few cases that reported young children having Cushing syndrome secondary to misuse of topical corticosteroids.